Anesthesiologists Play Key Role in Delivering PSH Concept for Hip Replacement Patients - Bittner, Dennis (MD Conference Express, 2014)
The perioperative surgical home is a multidisciplinary approach to caring for patients throughout the entire perioperative experience. This article discusses a PSH program developed at Ochsner Health System, New Orleans, Louisiana, USA, for patients undergoing elective hip arthroplasty.